Body weight reducing effect of oral boric acid intake. - AYŞAN, MUSTAFA ERHAN; Aysan, E; SAHIN, F; TELCI, D; YALVAC, ME; EMRE, SH; KARACA, C; MUSLUMANOGLU, M (My University, 2011)
Background: Boric acid is widely used in biology, but its body weight reducing effect is not researched. Methods: Twenty mice were divided into two equal groups. Control group mice drank standard tap water, but study group mice drank 0.28mg/250ml boric acid added tap water over five days. Total body weight changes, major organ histopathology, blood biochemistry, urine and feces analyses were compared. Results: Study group mice lost body weight mean 28.1% but in control group no weight loss and also weight gained mean 0.09% (p<0.001). Total drinking water and urine outputs were not statistically different. Cholesterol, LDL, AST, ALT, LDH, amylase and urobilinogen levels were statistically significantly high in the study group. Other variables were not statistically different. No histopathologic differences were detected in evaluations of all resected major organs. Conclusion: Low dose oral boric acid intake cause serious body weight reduction. Blood and urine analyses support high glucose, lipid and middle protein catabolisms, but the mechanism is unclear.
Keywords: Body weight